A Low Cost Process for Fabricating FDM Filaments Reinforced with Inorganic Fillers - Hassanien, Mohamed (2021)
A Master of Science thesis in Mechanical Engineering by Mohamed Hassanien entitled, “A Low Cost Process for Fabricating FDM Filaments Reinforced with Inorganic Fillers”, submitted in July 2021. Thesis advisor is Dr. Maen Alkhader and thesis co-advisor Dr. Bassam Abu-Nabah. Soft copy is available (Thesis, Completion Certificate, Approval Signatures, and AUS Archives Consent Form).